Mapping drivers, barriers, and trends in renewable energy sources in universities: a connection based on the SDGs - Henrique Lermen, Fernando (2024)
Universities play a pivotal role in modern society and must lead the way in achieving energy efficiency, directly contributing to the Sustainable Development Goals (SDGs). Like small towns in resource consumption and population mobility, many universities and research centers face significant challenges transitioning to renewable electricity systems. This study aims to (i) map the current scientific literature on renewable energy sources used by universities; (ii) discuss the drivers, barriers, and trends of implementing renewable energy; and (iii) establish a connection with the SDGs. More specifically, the authors conducted a systematic literature review based on three stages: (i) data collection, (ii) bibliometric analysis, and (iii) content analysis. Forty-two articles were obtained and defined as the studied sample. The findings of this review illuminate critical research themes, leading countries in renewable energy adoption, and the prevalent electricity sources, shedding light on the primary authors shaping the discourse. Wind and solar energy exhibit a notable growth trajectory, offering environmentally friendly alternatives compared to conventional sources. Furthermore, it is essential to highlight that the distribution of research documents in the sample is uneven, with a predominant concentration in European countries. Additionally, the study identifies the field’s key drivers, barriers, and emergent trends. The theoretical contributions encompass a comprehensive compilation of renewable energy sources, discernible research trajectories, and strategies to navigate obstacles. In practical terms, this work offers valuable insights for the selection of energy sources and stakeholder engagement, facilitating informed decision-making processes. This article’s novelty lies in its holistic examination of renewable energy adoption in university settings, providing a comprehensive overview of the current landscape and actionable insights for stakeholders seeking sustainable energy solutions within these institutions. This aligns with multiple SDGs, including Goal 7 (Affordable and Clean Energy), Goal 11 (Sustainable Cities and Communities), and Goal 13 (Climate Action), underscoring the critical role of universities in driving sustainable development.